Useful Methods for Targeted Plant Selection in the Discovery of Potential New Drug Candidates - Schwikkard, Sianne L.; Mulholland, Dulcie A. (Planta Medica, 2014)
The efficient and effective selection of appropriate plants for investigative purposes in a drug discovery program is of crucial importance for a successful outcome. A variety of approaches have been used by researchers with varying levels of success. A variety of different approaches to plant selection are discussed, including the ethnomedicinal approach, some ecological approaches, and the use of combinatorial and computational methodologies.
Keywords: biodiversity; targeted selection; ethnomedicine; drug discovery